A heuristic approach for location problems - Luis, Martino (2011)
This talk presents facility location problems that may arise in public or private sectors. Facilities can be constructed either on a plane or a network to satisfy one or more criteria. In this talk, a basic taxonomy of location problems is provided to give some initial ideas on location problems. A heuristic approach based on constructive scheme is introduced to deal with the problem. Other heuristic techniques, such as metaheuristics and hyperheuristics are also briefly presented. Some relevant literatures are comprehensively reviewed to map the problem. Some research avenues that worth noting to be explored in the future are also highlighted.